Social policy review. edited by Menno Fenger, John Hudson and Catherine Needham. - Fenger, Menno; Hudson, John, 1972-; Needham, Catherine, 1974- (Policy Press, 2016)
Published in association with the SPA, with specially commissioned reviews of pensions, health care, conditionality and housing, and including a themed section on personalised budgets, this book examines important debates in the field.